POLA PENGGUNAAN LAHAN DAN KOMPONEN PENYUSUN AGROFORESTRI HUTAN LINDUNG MUTIS TIMAU - Yakub Benu; Melkianus Pobas (Partner, 2020)
This research is aimed to comprehend the agroforestry land use pattern dynamics and composer components of Mutis Timau protected forest, and was held at Fatukoto and Ius Mollo village of Mollo Utara Subdistrict of Timor Tengah Selatan Regency of East Nusa Tenggara Province in January until April 2014. The primary data of the pattern was collected through observation and analyzed by grouping while the composer components through direct measurements and analyzed by calculation of volume, Shannon-Wiener biodiversity index, and stand projection with Sexy-fs tool. The stand kind and age secondary data were from the Forestry Agency of TTS Regency. The pattern dinamics were agrosilvopastural utilization at the young stand and livestock grazing silvopastural at the medium and old age stand. Young stand was combined with greenery food plants, while medium with graze and fruit crops plants, and the old one without combination practice. The composer components consisted of 20 kind and total 16,128 species and 1,709.12 m3of volume, which comprised with 11,976 species and 12 m3wooden vegetation of the young, medium 3,963 and 380,16 m3, and the old 189 species and 1316,96 m3.